Tonic modulation of spinal hyperexcitability by the endocannabinoid receptor system in a rat model of osteoarthritis pain - Sagar, Devi Rani; Staniaszek, Lydia E.; Okine, Bright N.; Woodhams, Stephen; Norris, Leonie M.; Pearson, Richard G.; Garle, Michael J.; Alexander, Stephen P.H.; Bennett, Andrew J.; Barrett, David A.; Kendall, David A.; Scammell, Brigitte E.; et al. (Wiley, 2010)
Objective. To investigate the impact of an experimental model of osteoarthritis (OA) on spinal nociceptive processing and the role of the inhibitory endocannabinoid system in regulating sensory processing at the spinal level. Methods. Experimental OA was induced in rats by intraarticular injection of sodium mono-iodoacetate (MIA), and the development of pain behavior was assessed. Extracellular single-unit recordings of wide dynamic range (WDR) neurons in the dorsal horn were obtained in MIA-treated rats and saline-treated rats. The levels of endocannabinoids and the protein and messenger RNA levels of the main synthetic enzymes for the endocannabinoids (N-acyl phosphatidylethanolamine phospholipase D [NAPE-PLD] and diacylglycerol lipase [DAGL]) in the spinal cord were measured. Results. Low-weight (10 gm) mechanically evoked responses of WDR neurons were significantly (P < 0.05) facilitated 28 days after MIA injection compared with the responses in saline-treated rats, and spinal cord levels of anandamide and 2-arachidonoyl glycerol (2-AG) were increased in MIA-treated rats. Protein levels of NAPE-PLD and DAGL, which synthesize anandamide and 2-AG, respectively, were elevated in the spinal cords of MIA-treated rats. The functional role of endocannabinoids in the spinal cords of MIA-treated rats was increased via activation of cannabinoid 1 (CB1) and CB2 receptors, and blockade of the catabolism of anandamide had significantly greater inhibitory effects in MIA-treated rats compared with control rats. Conclusion. Our findings provide new evidence for altered spinal nociceptive processing indicative of central sensitization and for adaptive changes in the spinal cord endocannabinoid system in an experimental model of OA. The novel control of spinal cord neuronal responses by spinal cord CB2 receptors suggests that this receptor system may be an important target for the modulation of pain in OA.